The mediating role of entrepreneurship education on the relationship between entrepreneurial attitude and entrepreneurship intention / Mohd Zamri Abu Bakar, Suffian Hadi Ayub and Norazwa Yeop Kamarudin. - Abu Bakar, Mohd Zamri; Ayub, Suffian Hadi; Yeop Kamarudin, Norazwa (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2020)
Past studies suggested that entrepreneurship is a key to economic growth and a potential force to exponential economic development. Entrepreneurship has also been identified as the solution to unemployment and a choice of career option. This paper examined Entrepreneurship Education (EE) and its mediation role in the relationship between Entrepreneurial Attitude (EA) and Entrepreneurship Intention (EI) among Malaysian university students. The study employed a quantitative research design with self-administered questionnaires adopted from past research, and administered to 120 students from universities in Malaysia. Smart PLS software was then utilised to attain the ideal Structural Equation Modelling (SEM) in confirming the hypotheses of study. The results showed EA has no direct effect nor influence on EI. However, for mediating interaction of EE, the results further showed that EE significantly mediates the relationship between EA and EI. This proves that EE, prior graduation has positive effect and leads to behaviour intention among Malaysian students towards choosing entrepreneur as their first career option.